Love as harm reduction: fighting AIDS and stigma in Vietnam - Small Dan (BMC, 2009)
Abstract In the summer of 2009, I visited a humble orphanage for children with HIV/AIDS in Vietnam. Here, like many parts in the world, the very existence of marginalized people with stigmatized illness is hidden away. Relegated to the shadows of society, these children lacked something more fundamental than housing, shelter, nutrition and medications. They lacked families to love and care for them unconditionally. One might think it self-evident that a visit to an orphanage for children with HIV would be profound, but the profundity wasn't where I expected to find it. It was in how the children had created their own family, loving each other like brothers and sisters, and the way the priest who operated the shelters was more than a Father, he was a dad to dozens of children. This is an account of love as harm reduction in the Mai Tam orphanage in Ho Chi Minh City.